Functional Analysis of TM6 MADS-box gene in the Octoploid Strawberry by CRISPR/Cas9 directed mutagenesis - Martín-Pizarro, Carmen; Triviño, Juan Carlos; Posé-Padilla, David (bioRxiv, 2018)
The B-class of MADS-box transcription factors has been studied in many plant species, but remain functionally uncharacterized in the Rosaceae family. APETALA3 (AP3), a member of this class, controls the identity of petals and stamens in Arabidopsis thaliana. In this work, we identified two members of the AP3 lineage in the cultivated strawberry (Fragaria x ananassa): FaAP3 and FaTM6. Interestingly, FaTM6, and not FaAP3, shows an expression pattern equivalent to that of AP3 in Arabidopsis. Genome editing using Cluster Regularly Interspaced Short Palindromic Repeats (CRISPR)/Cas9 system is becoming a robust tool for targeted and stable mutagenesis of DNA. However, whether it can be efficiently used in an octoploid species such as F.  ananassa is not known. Here we report for the first time the application of CRISPR/Cas9 in F. x ananassa to characterize the function of FaTM6 in flower development. An exhaustive analysis by high-throughput sequencing of the FaTM6 locus spanning the target sites showed a high efficiency genome editing already in the T0 generation. The phenotypic characterization of the mutant lines indicates that FaTM6 plays a key role in petal and especially in anther development in strawberry. Our results validate the CRISPR/Cas9 strategy for gene functional analysis in an octoploid species such as F. x ananassa, and offer new opportunities for engineering strawberry to improve traits of interest in breeding programs.
Keywords: Fresas - Variedades; Strawberry; CRISPR/Cas9; Transcription Factor; TM6